Optimal CO2 intake in metastable water film in mesoporous materials - Gen Li; Yong Tao; Xinping Zhu; Yining Gao; Peiliang Shen; Binbin Yin; Romain Dupuis; Katerina Ioannidou; Roland J.-M. Pellenq; Chi Sun Poon (Nature Communications)
Abstract The feasibility of carbon mineralization relies on the carbonation efficiency of CO2-reactive minerals, which is largely governed by the water content and state within material mesopores. Yet, the pivotal role of confined water in regulating carbonation efficiency at the nanoscale is not well understood. Here, we show that the maximum CO2 intake occurs at an optimal relative humidity (RHopt) when capillary condensation initiates within the hydrophilic mesopores. At this transition state, the pore becomes filled with metastable low-density water, providing an ideal docking site for CO2 adsorption and forming a mixed metastable state of water/CO2. We prove that RHopt depends on the mesopore size through a Kelvin-like relationship, which yields a robust engineering model to predict RHopt for realistic mineral carbonation. Building upon classical theories of phase transition in hydrophilic mesopores, this study unveils the capacity of the metastable water in CO2 intake and enhances the high-efficiency carbon mineralization with natural ore and industrial wastes in real-world applications.